Analysis of mechanical and thermal characterization of hexagonal boron nitride using a molecular dynamics simulation with the new Dreiding force field - Oh, Yuna; Jung, Hana; Bae, Kwak Jin; Kim, Yonjig; Yu, Jaesang (Taylor & Francis, 2022)
The Dreiding force field, which is used in molecular dynamics (MD) simulation, was newly developed to predict accurately the mechanical and thermal properties of hexagonal boron nitride (h-BN). The newly proposed Dreiding force field (N-DFF) has the force constants obtained from linear least square fitting and represents the system energy with more accuracy between the potential energy estimated by density functional theory and MD regarding the deformation of BN sheet. The mechanical and thermal properties of BN sheets obtained using N-DFF matched well the experimental and theoretical results. The N-DFF gives the best prediction of material properties of BN sheets.